Coagulation Abnormalities in Chronic Liver Disease - Franchini, Massimo; Mannucci, Pier Mannuccio (Seminars in Thrombosis and Hemostasis, 2025)
Chronic liver disease is a frequently encountered disorder and a major concern worldwide with a complex pathophysiology, which often affects the hemostatic system. Such alterations, which affect both primary and secondary hemostasis, are heterogenous, including prohemorrhagic (i.e., decreased coagulation factors, increased fibrinolysis, thrombocytopenia, and platelet dysfunction) and prothrombotic (i.e., decreased natural anticoagulants) changes. As a consequence of this unstable balance, patients with liver cirrhosis may experience both hemorrhagic complications and venous thromboembolic events, which are often unpredictable and whose management is particularly challenging for clinicians. This narrative review will address the most recent advances in the pathophysiology of key derangements of hemostasis in patients with chronic liver disease, focusing on their clinical implications and management.
Keywords: coagulation; hemostasis; liver cirrhosis; bleeding; thrombosis